The Effect of Non-Performing Loans and Capital Adequacy Ratio on Return on Assets of Banking Institutions Listed on The Indonesia Stock Exchange (2020–2023) - Mutiara Lusiana Annisa; Ruth Samantha Hamzah (LPPM STIE KRAKATAU, 2025)
This study aims to examine the effect of Non-Performing Loans (NPL) and Capital Adequacy Ratio (CAR) on Return on Assets (ROA) in banking institutions listed on the Indonesia Stock Exchange (IDX) during the period 2020–2023. A quantitative approach was employed using multiple linear regression analysis, with data collected from 22 banks over four consecutive years. The results show that NPL has a significant negative impact on ROA, indicating that a higher proportion of problematic loans tends to reduce bank profitability. On the other hand, CAR does not exhibit a significant influence on ROA, suggesting that the level of capital held by a bank does not necessarily translate into higher returns. These findings imply that asset quality plays a more crucial role in determining financial performance than capital adequacy, particularly during periods of economic crisis and recovery. Overall, this study contributes to a deeper understanding of the key factors influencing bank performance in the context of economic uncertainty following the COVID-19 pandemic.